Carousel sebagai Metode Narasi Visual dalam Jurnalisme Digital: Analisis Perubahan Format Penyampaian Berita di Platform Media Massa - Radit Tri Imansyah; Edy Suisno (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
The rapid growth of Instagram news production has created a journalistic problem: news must be delivered in concise, visual, and sequential formats while still maintaining accuracy, context, and editorial coherence. This study aims to analyze how carousel posts function as a visual narrative format in digital journalism and how the format changes the structure of news delivery. This research uses a qualitative approach with qualitative content analysis of 15 carousel news posts uploaded from January to March 2026 by five Indonesian Instagram news accounts: @malakaproject.id, @tempodotco, @cnnindonesia, @ussfeeds, and @totalpolitikcom. The analysis examines the function of opening slides, core slides, closing slides, the relationship between visual elements and short text, and transitions between slides. The findings show that carousel posts do not merely visualize news, but organize information into connected narrative units. Opening slides function as attention hooks, core slides build context and chronology, while closing slides provide summary or interpretive emphasis. The swipe mechanism shapes rhythm, suspense, and continuity. These findings indicate a shift in digital journalism from linear text-based narration toward sequential visual narration that requires active audience movement, careful editorial selection, and stronger control over context so that news remains coherent, complete, and accountable within platform-based communication.